O Novo Cinema Negro importa: cultura e política nas imagens de Os Donos da Rua (John Singleton, 1991) e Febre da Selva (Spike Lee, 1991) - Brandão, João Lucas França Franco (2019)
Film production by black directors in the United States peaked in 1991, when at least 17 of them entered the national cinema circuit - a number larger than the previous decade. We are talking about a movement called New Black Cinema. In this scenario, names like Spike Lee and John Singleton stood out as promising directors of this generation by reconciling their own cinematic aesthetics and a very strong discursive power for the benefit of the African-American community. In this way, this work examines two of these filmmakers, Boyz n the Hood’ and Jungle Fever, Singleton and Lee, respectively, who in 1991 raised questions such as the segregation of urban space, blackness, masculinity of the young black and interracial relationships, for example. Our goal, therefore, from a perspective of Visual History, is to analyze these images, the agency representations and the images/speeches that served as reference for the construction of these films, in order to verify the contradictions of the American society, the vision of Singleton and Lee about some of the narrative themes and how the audience received them. It is also our aim to understand in the images and in the society that looks at them, the political struggles and the representational struggles that are so important to the social dynamics in which the African-American is inserted.